Conservation’s green illusion: Nitrogen thresholds as critical determinants of extinction risk in specialist herbivores - Saroj Shrestha (Global Ecology and Conservation)
Despite decades of habitat-based interventions, the red panda (Ailurus fulgens) remains in steep decline across its Himalayan range. Conservation strategies have emphasized forest cover and connectivity yet overlooked a key physiological constraint: the availability of dietary nitrogen. As obligatory bamboo folivores, red pandas depend on leaves with sufficiently high foliar nitrogen to meet metabolic and reproductive demands, though direct experimental evidence is limited. However, bamboo nitrogen content varies dramatically across species, seasons, elevations, and disturbance gradients. This perspective argues that the absence of nitrogen criteria constitutes a critical blind spot in red panda conservation. Sub-threshold habitats can function as ecological traps, silently undermining translocation, reproduction, and survival even in structurally intact forests. We call for a paradigm shift that integrates foliar nitrogen thresholds into conservation science, landscape planning, and reintroduction protocols. We outline research priorities to (1) establish red panda nitrogen requirements through controlled trials, (2) map nitrogen landscapes using NIRS and remote sensing, and (3) embed nutritional adequacy in habitat policy frameworks. Without this integration, conservation efforts risk being structurally sound but nutritionally void.